Denitrogenative Pd/Cu-catalyzed Suzuki-type cross-coupling of Aryltrifluoroborates with Arylhydrazine hydrochlorides in water under room temperature - Wang, Guofang; Cheng, Kai (Applied organometallic chemistry, 2018)
A water-soluble palladium-catalyzed Suzuki-type cross-coupling of aryltrifluoroborates with arylhydrazide hydrochlorides was efficiently developed under mild and environmentally benign conditions, in water without any ligand. The newly developed Pd/Cu co-catalyzed denitrogenative reaction gave a range of structurally diverse substituted biaryls with good to excellent yields, in which the byproduct was nitrogen.